TINJAUAN PENGEMBANGAN KURIKULUM IPS DI SEKOLAH DASAR - Yulfia Nora; Nurhizrah Gistituati; Alwen Bentri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Social science learning education describes the development of the social science curriculum for every school level in Indonesia. IPS learning education and development have a dynamic and polemic history in Indonesia. The review of IPS learning education and development has a historical method that can explain the development of IPS learning education adapted from the pioneers of IPS educational development, America and England, as a reference for IPS learning education in Indonesia. The development of social science learning education in Indonesia is based on the condition of the Indonesian community and government. Hence, it influences the monitoring and revision of the social science learning education curriculum in Indonesia. The research used literature reviews collected based on several journal reviews that are historically grouped based on a review of the social science curriculum use in elementary school. The results indicate that IPS educational education requires the development of technological sophistication that involves the community as an object of social learning education and development. Clearly, the development of social learning education requires the involvement of the current development in line with the sophistication of technology and society to be developed dynamically on social science in Indonesian education.